FLORA OF SINGAPORE PRECURSORS, 8. SYSTEMATY OF THE NEW SOUTHEAST ASIAN GENERA CANTHIUMERA AND DIBRIDSONIA (RUBIACEAE: VANGUERIEAE), WITH NOTES ON PLANT ARCHITECTURE AND REPRODUCTIVE ECOLOGY - Wong Khoon Meng; Ridha Mahyuni; Xin Yi Ng; Louise Neo (REINWARDTIA, 2018)
WONG, K. M., MAHYUNI, R., NG, X. Y. & NEO, L. 2018. Flora of Singapore Precursors, 8. Systematy of the new Southeast Asian genera Canthiumera and Dibridsonia (Rubiaceae: Vanguerieae), with notes on plant architecture and reproductive ecology. Reinwardtia 17(2): 101–124. — The recognition of a number of distinct genera by morphological and molecular phylogenetic attributes from the Canthium s.l. complex still leaves a core group of morphologically disparate taxa. The distinguishing features of the spiny Canthium s.s. and two groups of non-spinescent Southeast Asian tree taxa still commonly identified with C. glabrum Blume and C. confertum Korth. are assessed against those of Cyclophyllum Hook.f., Bullockia (Bridson) Razafim., Lantz & B.Bremer, Kanapia Arriola & Alejandro, Keetia E.Phillips, Perakanthus Robyns ex Ridl., Psydrax Gaertn., and Pyrostria Comm. ex Juss., similarly arborescent genera that have been so distinguished through recent studies. Canthium glabrum and C. confer-tum are, respectively, the bases of the genera Canthiumera K.M.Wong & Mahyuni and Dibridsonia K.M.Wong newly described here. The new species Canthiumera robusta K.M.Wong & X.Y.Ng is described; new nomenclatural combi-nations include C. glabra (Blume) K.M.Wong & Mahyuni, C. neilgherrensis (Wight) K.M.Wong, C. neilgherrensis var. chartacea (Gamble) K.M.Wong, C. siamensis (K.Schum.) K.M.Wong, Dibridsonia conferta (Korth.) K.M.Wong, D. culionensis (Elm.) K.M.Wong, and D. oblongifolia (Quisumb. & Merr.) K.M.Wong. Canthium glabrum var. pedun-culatum Pitard, Plectronia neilgherrensis var. chartacea Gamble and Canthium confertum Korth. are lectotypified. Plectronia viridis Merr. and P. leytensis Merr. are reduced to synonymy under Dibridsonia conferta. Notes on the tree architecture, dispersal ecology and germination of Canthiumera and Dibridsonia are provided.